Market Penetration Strategies of Mixue Ice Cream & Tea in Emerging Markets : A Case Study of Laos - Kommadam, Khonexai; Thu, Khin Myat (Aurora: Journal of Emerging Business Paradigms, 2024)
This study examines the market penetration strategies of Mixue Ice Cream & Tea in Laos, an emerging market in Southeast Asia. Using a qualitative case study approach, data were collected through semi-structured interviews with key stakeholders, including franchise owners, management representatives, and local distribution partners, supplemented by secondary data from company reports, industry publications, and market research. The findings reveal that Mixue’s success in Laos is driven by a combination of low-cost pricing, culturally relevant product adaptations, and an efficient franchise-based distribution model. These strategies have allowed the brand to effectively penetrate the Lao market, overcoming challenges posed by infrastructure limitations and competitive pressures. The study also demonstrates the importance of balancing global brand consistency with local customization, as Mixue has successfully adapted its marketing and product offerings to align with the preferences of Lao consumers while maintaining the core elements of its global identity. However, the company’s continued growth will depend on its ability to innovate and respond to evolving consumer preferences and increased competition in the market. The findings contribute to the literature on global brand adaptation and market penetration in emerging markets, offering practical insights for other businesses looking to expand in similar contexts.